PREVALENCE, MANAGEMENT AND OUTCOME OF MULTIDRUGS RESISTANT TUBERCULOSIS : A COMPREHENSIVE SYSTEMATIC REVIEW - Sijabat, Landong; Novettiandari, Guinanti (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Multidrug-resistant or rifampicin-resistant TB (MDR/RR-TB), is an important obstacle to global TB control. The failure to diagnose and effectively treat MDR/RR-TB patients perpetuate ongoing MDR/RR-TB transmission in the community and can amplify the MDR/RR-TB burden. The aim: The aim of this study to show about prevalence, management and outcome of multidrug resistant tuberculosis. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion:  The success of any national program can only be ascertained by studying the outcomes of treatment regimes in patients with MDR-TB enrolled in different DOTS-plus sites of the country.